2019
DOI: 10.1088/1755-1315/272/3/032170
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Communicative Grammar to Technical University EFL Learners

Abstract: The paper considers communicative approach to grammar as a means to develop the Technical University EFL learners’ ability to communicate with each other focusing on the language meaning rather than on the form. Although the communicative approach is not ideal, it makes the communication in the classroom natural, thus creating conditions for self-realization, motivation and meaningful language acquisition. The paper establishes principles to be applied when teaching grammar communicatively. They concern two as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Communicative language teaching (CLT) is an approach to the teaching of second and foreign languages that focuses on meaningful communication in real life as a means and the goal of learning a language (Baydikova & Davidenko, 2019). CLT originated in Europe during the 1970s when the revolution of British language teaching took place and linguists began to focus on communicative competence rather than on grammatical competence which paid much attention to the mastery of structures.…”
Section: Communicative Language Teaching (Clt)mentioning
confidence: 99%
See 3 more Smart Citations
“…Communicative language teaching (CLT) is an approach to the teaching of second and foreign languages that focuses on meaningful communication in real life as a means and the goal of learning a language (Baydikova & Davidenko, 2019). CLT originated in Europe during the 1970s when the revolution of British language teaching took place and linguists began to focus on communicative competence rather than on grammatical competence which paid much attention to the mastery of structures.…”
Section: Communicative Language Teaching (Clt)mentioning
confidence: 99%
“…Klimova, Klimova, and Dubinka (2019) and his team studied how to improve students' communicative ability in business English, and they found CLT as the main teaching method that could help learners apply vocabulary and grammar structures accurately and spontaneously in speech. Baydikova and Davidenko (2019) tried to propose some specific principles for teaching communicative grammar and his study focused on the pre-communicative activities and communicative activities in class. This study concluded that CLT was a method to improve EFL learners' competence to interact in different contexts which simulated real-life interaction, motivated students' communication, and implied language for meaningful uses (Baydikova & Davidenko, 2019).…”
Section: Clt In Grammar Teachingmentioning
confidence: 99%
See 2 more Smart Citations
“…By applying those steps, the students can implement their grammar usage knowledge into conversation. Baydikova & Davidenko (2019) emphasized that teaching language focuses on using it in communication to boost speaking fluency. It would be meaningful rather than learning the form of it.…”
Section: Introductionmentioning
confidence: 99%